Insights into the heat contributions and mechanism of CO2 adsorption on metal–organic framework MIL-100 (Cr, Fe): Experiments and molecular simulations - Teerachawanwong P. (2023)
Metal–organic frameworks (MOFs) MIL-100 (Cr, Fe) synthesized by the hydrothermal method were subjected to heat treatment under an H2 flow. The MIL-100 (Cr) samples had specific surface areas and pore volumes approximately-two times higher than those of the MIL-100 (Fe) samples. The H2 heat treatment enhanced the crystallinity, especially for MIL-100 (Fe). The resulting adsorbents exhibited a superior CO2 adsorption capacity. Furthermore, the grand canonical Monte Carlo method was used to examine the adsorption mechanism at a molecular level. The heat contribution of each atom type of MOFs was demonstrated. The highest heat was found at low loadings (Henry's law region) among other regions owing to CO2 adsorption inside the supertetrahedron. The most active atoms were C atoms (C[sbnd]O > C[sbnd]C > C[sbnd]H), followed by the O atom (C[sbnd]O[sbnd]unsaturated metal), the unsaturated metal site, the other O atom (C[sbnd]O[sbnd]saturated metal), the saturated metal site, the H atom of the ligands, and the O atom of the metal cluster, respectively. This study can provide insights into the determination of the atomic heat contributions of other adsorbents for a better understanding of material design and the mechanism of adsorption.